ASSESSMENT ON RISK-BASED MARKETING OF BIO-OSD PRODUCT FOR HANDLING OIL SPILLS AT THE WATER SURFACE - Miftah Fauzi , Anas; Hambali, Erliza; Yani, Mohamad; Irawan, Andre; Febriantini, Dwi; Pebriani, Siska (Department of Agroindustrial Technology, Bogor Agricultural University, 2024)
Oil spills during exploration and transportation can pollute the land and water environment. Oil Spill Dispersants (OSD) are needed to disperse petroleum spills, thus facilitating the subsequent handling process. Bio-OSD is an environmentally friendly product because it uses surfactants derived from palm oil. This study aims to obtain information about the marketing strategy for Bio-OSD products by considering market potential and marketing risks as one of the important stages in the commercialization process. The research was carried out by analyzing the needs and availability, form of the market, and conditions of competitors for the Bio-OSD product and designing a risk-based marketing strategy through a mix between Segmenting, Targeting, Positioning (STP), and Product, Price, Place, Promotion (4P), as well as risk analysis. They were using the House of Risk (HOR) method. As a comparison, commercial OSD products were used. The results showed that the Bio-OSD product gave positive and superior values ​​in terms of quality and price parameters compared to commercial OSD products, so it was feasible to be commercialized. The B2B marketing strategy design results in segmentation and target markets aimed at PT Pertamina (Persero) subsidiaries, as well as product positioning as a diversified product. The marketing mix design resulted in products that meet the needs standards, with a price range of IDR 50,000-IDR 80,000/L, target sales in Java, and promotions carried out both online and offline. The marketing risk management plan indicates three priority risk mitigation actions namely; regular monitoring and analyzing of marketing data, training and development for improving workers capability, and expanding promotional media. Keywords: OSD, surfactant, palm oil, risk, marketing